Methylprednisone administration epidural via as an alternative treatment to control pain in equine tail syndrome in bitch with lumbosacral instability: case report - de Moura Macedo, Thais; BESSI, W.H. (Pubvet, 2020)
Labor refers to the equine tail syndrome in dogs with an emphasis on clinical, noninvasive treatment for pain control. The equine tail is a collection of nerve roots that discovers the vertebral canal at the end of the spinal cord, mainly affecting large dogs. Conservative treatment is an option over surgical treatment. In view of this, this report shows the effect of the use of epidural applications of methylprednisone in three applications with interval of twenty-one days.
Keywords: Cauda equina syndrome; analgesia